P2.127 Presentation of Lymphogranuloma Venereum (LGV) in 2012 in the Reference STI Unit of Barcelona. (13th July 2013) - Arando, M; Vall, M; Armengol, P; Caballero, E; Barberá, M
Abstract : Since 2003 LGV outbreaks have been reported in different European cities in men who have sex patient men with high-risk sexual behaviours. In the majority of cases the most common clinical presentation was a rectal syndrome described as an acute proctitis. In Barcelona during 2012 the most common clinical presentation was proctitis, but revealed an increase in cases of LGV extrarectal location. Objective: To analyse LGV cases that have been diagnosed in 2012 in the reference STI Unit (UITS) Drassanes of Barcelona. Methods: Retrospective descriptive study. Review of epidemiological data, clinical presentation, physical examination and results of mentioned cases has been conducted. Results: In 2012 fifty-two cases of LGV in UITS were diagnosed, 8 of them in an extrarectal location. All of them were male: 50 were MSM and 2 bisexual men. Co-infection with HIV was 65%, decreasing to 50% in the extrarectal location. 11.5% of them had a history of previous LGV and 36.5% had a sexually transmitted infection in the previous 12 months. The most common clinical presentation was proctitis (65%), other clinical manifestations were urethritis, inguinal syndrome and anogenital ulcers. 21% were diagnosed by contact study (half for LGV and half for other STI) and one case was diagnosed by screening in an asymptomatic patient. Discussion: Although during the last years the typical presentation of LGV has been proctitis, the extrarectal location has increased considerably in 2012. In this situation it is necessary to assess whether or not to request it in a urethral syndrome as ulcerative lesions, especially in men who have sex with men with high-risk sexual behaviours.